2002
DOI: 10.1542/peds.109.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Infant Heart Transplantation at Stanford: Growth and Neurodevelopmental Outcome

Abstract: Multicenter prospective longitudinal neurodevelopmental outcome studies of infant heart transplant patients should be conducted to provide a more efficient basis for evaluating management protocols and assessment of long-term outcomes and of the need for early intervention services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
34
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…Delayed psychomotor development is frequently reported in studies of infant HTx recipients. 2,6,14 The only studies assessing older children with HTx on a copying task found visuomotor functions were in the low-average range, 3 and visuospatial performance was in the clinically significant range. 7 Immunosuppressive medication may cause tremor, 27 which may account for part of this impairment, but children with surgically corrected heart diseases and children on the waiting list for heart or heart-lung transplant do show fine motor and visuospatial difficulties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Delayed psychomotor development is frequently reported in studies of infant HTx recipients. 2,6,14 The only studies assessing older children with HTx on a copying task found visuomotor functions were in the low-average range, 3 and visuospatial performance was in the clinically significant range. 7 Immunosuppressive medication may cause tremor, 27 which may account for part of this impairment, but children with surgically corrected heart diseases and children on the waiting list for heart or heart-lung transplant do show fine motor and visuospatial difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Older children have cognitive and academic performance in the low-average to average range. [3][4][5][6][7] As many as 15% to 46% of children undergoing HTx perform, in general, 2 standard deviations (SD) below test norms, indicating significant cognitive delays. [3][4][5]8 Most studies in the field of pediatric HTx have assessed only global intelligence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fleisher and colleagues found that only 58% of heart transplant patients and 40% of age-matched comparison patients with CHD had normal expressive language scores. 20 One proposed explanation is that these infants are sometimes hospitalized for long periods during infancy, when many language skills are acquired. 21 Wray and Radley-Smith suggested that parental overprotection and restrictions limit the child's social interactions and impact the development of speech and socialization skills, resulting in poorer performance in these areas for young patients in both illness groups compared with the healthy group, and in the CHD group compared with the cardiomyopathy group.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] This can include patients with congenital lesions not amenable to surgical palliation, 5,6 or those who have failed attempts at surgical palliation. Although long-term survival and good clinical outcomes are possible in infants, 1,7 these children continue to face a considerable scarcity of donor organs and encounter extensive waiting periods.…”
mentioning
confidence: 99%